Urban Landscapes in Animated TV Serials: TV Fiction Format and Possible World in Arcane (2021–) - Encinas Cantalapiedra, Arturo (Street Art & Urban Creativity, 2024)
The first novelty of this article is an analysis of the animated TV show Arcane (2021–) based on fiction format theory from a narrative perspective. On average, each episode of Arcane: takes place over 22 scenes lasting about two minutes each; features around twenty settings, mostly urban; has roughly four plots that unfold with a high level of continuity; features about four main and twelve secondary characters. The format theory is drawn from possible worlds theory, which makes it possible to delve into the narrative and symbolic value of urban landscapes in the series. This is the article’s second contribution: showing how Arcane deals with the clash between the upper city of Piltover and the undercity of Zaun, two worlds defined by their spiritual and operational centres, reflecting different forms of understanding existence, and thus governed by different social orders.